The relationship between the application of the principles of banking governance and the appropriateness of the outputs of the accounting system - Qarib, Abeer Abdullah; Yousef, Aisha Mousa; Wadi, Amal Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2019)
The study examined the relationship between the application of the principles of governance and the appropriateness of the outputs of the accounting system, The importance of the study was to highlight the relationship between the appropriate accounting information and the application of the principles of governance in accounting systems in addition to supporting the users' confidence in the financial information issued by the financial statements by providing appropriate information for making the appropriate decision. And aimed to identify the principles of governance and the characteristics of the suitability of the outputs of the accounting system The study recommended that banks should apply the principles of governance to include all banks that have been in compliance with the principles of governance. As well as the need to prepare information and present it in a timely manner to enhance its suitability, with the need to give shareholders all the information, especially regarding unusual processes that affect their rights.
Keywords: banks; accounting; principles of bank governance; economy